Differences in perception of physical education teachers interaction style - Marcela Janíková (Czech Pedagogical Society, 2010)
The paper deals with the interaction style of physical education lowersecondaryteachers. It is based on Leary's Interpersonal Behavior Circle, which wasused to develop the Questionnaire on Teacher Interaction (QTI). This questionnairewas distributed to lower-secondary teachers of physical education (19) and to their pupils(889) in the regions of South Moravia, Zlin and Olomouc. The findings reflect thedifferences between the teachers' self-perception and the way the teachers are seen bythe pupils, gender differences in the teachers' interaction styles and differences causedby the length of practice and the nature of the school subject in which the study wascarried out.